HYBRID FINANCIAL REPORTS FOR WAQF PROJECTS TOWARDS ENHANCING ACCOUNTABILITY AND TRANSPARENCY OF WAQF INSTITUTIONS IN MALAYSIA: A CONCEPTUAL PAPER - Mohd Syazwan Karim; Sharifah Norhafiza Syed Ibrahim; Nur Farahah Mohd Pauzi; Khairiah Ahmad; Adriana Shamsudin; Azlan Md Thani (Journal of Islamic, Social, Economics and Development, 2022)
Nowadays, the number of waqf projects is on the rise in Malaysia. Several public universities have initiated and managed waqf projects in various sectors, including the agriculture sector. These waqf projects contribute significantly to the economic and social development of the country. Despite its increasing popularity and importance, the sustainability of waqf institutions may be jeopardized due to its poor accountability and transparency. The lack of suitable accounting standards and regulation could compromise the quality and comparability of accounting information. This research aims to propose a set of practical and applicable hybrid financial report for agriculture waqf projects with income generation prospects. The proposed conceptual model would be a tool that will help transform the conventional reporting into a more transparent financial reporting by integrating the conventional accounting standards and waqf accounting practices from various policy makers to enhance and enrich the good corporate governance practices. Consecutively, it will help policy makers in issuing comprehensive financial reporting guideline and framework for waqf institutions which ultimately would enhance the confidence level amongst waqf contributors for waqf funding as instruments for economic and social development